From fix to fitting: Connecting low-emission development with multilevel smallholder dairy practices in Kenya - Vernooij, Vera; Schoneveld, G.C.; Vellema, Sietze; Crane, Todd A.; Kihoro, Esther (Informa UK Limited, 2024)
Smallholder livestock production systems are targeted for climate change mitigation via Low-Emission Development Strategies (LEDS). LEDS promote the adoption of so-called best agricultural practices for mitigation gains, while also expecting to contribute to socio-economic development. However, the assumed alignment between LEDS and varied realities of smallholder farmers is not self-evident. This study argues for a shift away from problematizing the adoption of ideal-type and uniform LED-practices (or a “fix”) to fitting LEDS to diverse smallholder priorities and capabilities embedded in specific regional histories and conditions. To make this shift, we assess the plausibility of fit of LED-practices into diverse smallholder realities in Kenya’s dairy sector. A mixed-methods approach exposes variation in the use of LED-practices in diverse dairy practices at household and regional levels. We characterize smallholder heterogeneity by distinguishing six clusters through a multivariate analysis of data from 1009 households in three regions of Kenya, and present patterns in uptake and intensity of the use of LED-practices for each household type. Next, the combination of quantitative and qualitative data shows variation in uptake of LED-practices at the level of the three counties, which suggests the importance of regional conditions in shaping the uptake of LED-practices and places the adoption focus beyond household-level decision-making. Subsequently, we identify starting points for LEDS design attuned to variation in smallholder dairy realities at multiple levels, where we consider scale at the start, and shift attention from the adoption of fixes to the creation of spaces conducive to “fitting” LED-practices into diverse realities.